Pacing pattern and speed skating performance in competitive long-distance events - Mühlbauer, T.; Panzer, S.; Schindler, C. (The Journal of Strength and Conditioning Research, 2010)
The present study was aimed to compare the pacing pattern adopted by women and men in races performed during a complete World Cup series. Elite skaters competed in long-distance races of different length (3,000, 5,000, and 10,000 m) and location (low/high altitude) where distribution of lap times were analyzed. Regardless of athletes' performance level, gender, or rinks' location, similar pacing patterns were observed in each event, which were characterized by an initial acceleration followed by a progressive delay in lap times-"positive pacing strategy". Differences in lap times were significant in each instance for women's 3,000 m (p < 0.001). For the 5,000 m races, laps 5-12 in women and laps 8-12 in men were slower compared with previous laps (p < 0.001, for both sexes). For men's 10,000 m, skaters performed only the first lap faster than the remaining laps (p < 0.001) with laps 2-7 not different from each other but faster than laps 19-24 (p < 0.05), which also did not differ from each other. Top-ranked compared with bottom-ranked skaters (p < 0.001) and male compared with female skaters (p < 0.001) were significantly faster at each lap, suggesting that technical or physiological or both aspects need to be developed in those. The significantly shorter lap times at high- compared with low-altitude races (p < 0.001) suggest that rinks' location appears to be important for performance outcome, at elite level.